Hubungan pemenuhan kebutuhan belajar dengan kemampuan pemecahan masalah peserta didik Sekolah Dasar - Rahmadian, Rizqi Karisma; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Universitas Sebelas Maret, 2026)
This study investigated the correlation between the fulfillment of learning needs and students' problem-solving abilities in science instruction within elementary schools. The research was grounded in the urgency of 21st-century skills development, especially critical and problem-solving thinking, in response to the educational demands of the Industry 4.0 and Society 5.0 eras. A quantitative correlational survey design was applied. The population included elementary school students in Laweyan District. Data were gathered using a 4-point Likert-scale questionnaire to assess students’ perceptions of learning needs (readiness, interest, and learning profile) and open-ended questions to measure problem-solving ability (identification, alternative solutions, best solution implementation, and evaluation). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Findings revealed low but positive correlations between all aspects of learning needs and problem-solving skills. Readiness had the strongest correlation with generating alternative solutions (r = 0.220), while interest was most strongly linked to executing the best solution (r = 0.217). Learning profile showed the weakest associations across all indicators. The results emphasized that although learning needs are not dominant predictors, their integrated fulfillment contributes to improving problem-solving competence. The study concluded that comprehensive attention to students’ learning readiness, interest, and learning profiles supports the development of their problem-solving abilities.